2021
DOI: 10.1101/2021.01.11.425955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A modified fluctuation assay reveals a natural mutator phenotype that drives mutation spectrum variation withinSaccharomyces cerevisiae

Abstract: Mutations are the source of genetic variation and a prerequisite for evolution. Despite their fundamental importance, however, their rarity makes them expensive and difficult to detect, which has limited our ability to measure the extent to which mutational processes vary within and between species. Here, we use the 1011 Saccharomyces cerevisiae collection to measure variation of mutation rates and spectra among strains isolated from a variety of natural and human-related environments. The mutation spectra of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 105 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…Our discovery of a genetic modifier of the murine C>A mutation rate provides new support for the long-standing theoretical prediction that multicellular eukaryotes have a limited ability to optimize their germline replication fidelity 1 . Our work shows that common mutator alleles, previously identified only in microorganisms such as Saccharomyces cerevisiae 39,40 , also shape vertebrate genetic diversity.…”
Section: Discussionmentioning
confidence: 63%
“…Our discovery of a genetic modifier of the murine C>A mutation rate provides new support for the long-standing theoretical prediction that multicellular eukaryotes have a limited ability to optimize their germline replication fidelity 1 . Our work shows that common mutator alleles, previously identified only in microorganisms such as Saccharomyces cerevisiae 39,40 , also shape vertebrate genetic diversity.…”
Section: Discussionmentioning
confidence: 63%
“…They found that human triplet spectra distinctly cluster by continental ancestry group and that historical pulses in mutation activity influence the distribution of allele frequencies in certain mutation types. The divergence of mutation spectra among human continental groups has been replicated in independently generated datasets (7,16), and similar patterns have been observed in other species, including great apes (17), mice (18), and yeast (19). Some of the mutation spectrum divergence between mice and yeast lineages has been mapped to mutator alleles (19,20).…”
Section: Significancementioning
confidence: 56%
“…Both approaches have been used in different contexts with model organisms. In yeast, mutation rates and spectra have been shown to differ within and between species (Nguyen et al 2020; Jiang et al 2021), between environmental factors such as mild (Liu and Zhang 2019) and severe stressors (Shor et al 2013) and vary depending on ploidy (Sharp et al 2018) or sequence context (Ma et al 2012). A wide array of genes, notably involved in DNA repair, have been shown to influence the mutation landscape (Demogines et al 2008; Lang et al 2013; Serero et al 2014; Stirling et al 2014; Gou et al 2019; Loeillet et al 2020).…”
Section: Introductionmentioning
confidence: 99%